Family or otherwise: Exploring the impact of family motivation on job outcomes in collectivistic society - Yaqoob, Samina; Ishaq, Muhammad Ishtiaq; Mushtaq, Mamoona; Raza, Ali (Frontiers in Psychology, 2023)
The motive of the current research is to determine the influence of family motivation on intent to leave and job performance using self-determination theory. Moreover, this study also explores the moderating role of collectivistic culture and the mediating role of psychological meaningfulness on the relationship between family motivation and work outcomes during COVID-19 pandemic. The data were collected from 81 teams that comprised of 349 healthcare staff handling COVID-19 related projects in public hospitals of Pakistan. The findings revealed that family motivation enhanced employee job performance and lessened employees’ intent to leave. At the same time, family motivation and psychological meaningfulness are stronger in highly collectivistic cultures compared to less collectivist cultures. This study extends the investigation of the newly developed construct of family motivation (Menges et al., 2017) by focusing on psychological meaningfulness and collectivistic culture. This study provides several critical insights for the hospitals by exploring the importance of family motivation as a potential motivational resource for maintaining high employee job-performance levels and lessening the intent of employees to leave.